The Relationship Between Social Support and Academic Flow in Junior High School Students: Hubungan Antara Dukungan Sosial dengan Flow Akademik Pada Siswa Sekolah Menengah Pertama - Larasati, Nadya Ayu; Nastiti, Dwi (Universitas Muhammadiyah Sidoarjo, 2022)
This research is motivated by a phenomenon that occurs in students of SMP Muhammadiyah 8 Tanggulangin Sidoarjo where there are students who still do not show their academic flow. This study aims to determine whether there is a relationship between social support and academic flow in students of SMP Muhammadiyah 8 Tanggulangin Sidoarjo. This type of research is quantitative research with a correlational approach. The total population in this study was 174 students. The sampling technique used is a non-probability sampling technique in the form of saturated sampling so that the number of samples is 174 students. Data collection used two Likert model psychological scales, namely the social support scale and academic flow. Data analysis was done by using Pearson Product Moment correlation statistical technique and using SPSS 23.0 for windows program. The results of the analysis of this study indicate a correlation coefficient of rxy = 0.464 with a significance of 0.0000 (<0.05), meaning that there is a positive relationship between social support and academic flow. The higher the social support received by students, the higher the academic flow experienced by students, and vice versa, the lower the social support received by students, the lower the academic flow experienced by students. The magnitude of the effect resulting from the relationship between social support and academic flow in students of SMP Muhammadiyah 8 Tanggulangin Sidoarjo ranges from 0.3-0.5 in the medium category.